Comparative Study of the Antimicrobial Activity of Selenium Nanoparticles With Different Surface Chemistry and Structure - Filipović, Nenad; Ušjak, Dušan; Milenković, Marina T.; Zheng, Kai; Liverani, Liliana; Boccaccini, Aldo R.; Stevanović, Magdalena M. (Frontiers in Bioengineering and Biotechnology, 2021)
Although selenium nanoparticles (SeNPs) have gained attention in the scientific community mostly through investigation of their anticancer activity, a great potential of this nanomaterial was recognized recently regarding their antimicrobial activity. The particle form, size, and surface chemistry have been recognized as crucial parameters determining the interaction of nanomaterials with biological entities. Furthermore, considering a narrow boundary between beneficial and toxic effects for selenium per se, it is clear that investigations of biomedical applications of SeNPs are very demanding and must be done with great precautions. The goal of this work was to evaluate the effects of SeNPs surface chemistry and structure on antimicrobial activity against several common bacterial strains, including Staphylococcus aureus (ATCC 6538), Enterococcus faecalis (ATCC 29212), Bacillus subtilis (ATCC 6633), and Kocuria rhizophila (ATCC 9341), as well as Escherichia coli (ATCC 8739), Salmonella Abony (NCTC 6017), Klebsiella pneumoniae (NCIMB 9111) and Pseudomonas aeruginosa (ATCC 9027), and the standard yeast strain Candida albicans (ATCC 10231). Three types of SeNPs were synthesized by chemical reduction approach using different stabilizers and reducing agents: (i) bovine serum albumin (BSA) + ascorbic acid, (ii) chitosan + ascorbic acid, and (iii) without stabilizer + glucose as reducing agent. A thorough physicochemical characterization of the obtained SeNPs was performed to determine the effects of varying synthesis parameters on their morphology, size, structure, and surface chemistry. All SeNPs were amorphous, with spherical morphology and size in the range 70-300 nm. However, the SeNPs obtained under different synthesis conditions, i.e. by using different stabilizers as well as reducing agents, exhibited different antimicrobial activity, which is crucial for their applications. In this paper, the antimicrobial screening of the selected systems is presented, which was determined by broth microdilution method and inhibitory influence on the production of monomicrobial and polymicrobial biofilm was evaluated. The potential mechanism of action of different systems is proposed.